I dreamed I was Emily Dickinson's boyfriend : poems - Koertge, Ronald (Red Hen Press, 2022)
"I Dreamed I Was Emily Dickinson's Boyfriend easily solidifies his reputation as a poet who is very funny and also very serious. In these surprising and delightful poems, a mannequin joins the Me Too movement, a summer job turns into a lesson in class distinctions, and Jane Austen makes a surprise appearance at a mall. Ron Koertge's uniquely playful imagination is on display in poem after poem"--